The Carbon Sequestration Potential of Soils: Some Data from Northern Italian Regions - Ciro Gardi; Stefano Brenna; Silvia Solaro; Mauro Piazzi; Fabio Petrella (Italian Journal of Agronomy)
It is well known that soil plays, within terrestrial ecosystems, an essential role in many biogeochemical cycles and in the regulation of greenhouse gas fluxes. Less known, and often underestimated, is the importance of carbon sequestration potential of soil, especially trough humified carbon. Even within the agro-forestry practices of the Kyoto Protocol, most of the attention is devoted to the biomass carbon storage, rather than soil carbon sequestration. The highest potentialities for carbon sequestration are related to the arable lands, that accounts for the 11% of earth surface; the increase of 0.1% of organic carbon content in the 0-30 cm layer of cultivated soils, achievable with minor adjustment of agronomic practices, is equivalent to the sequestration of 5,000 millions t of carbon. On the other hand, the conversion of a grasslands into cultivated land determine, during 50-70 years, a release of 80-150 t CO2 ha-1.Within this paper the estimate of soil organic carbon of three Northern Italian regions is presented.